2010
DOI: 10.1200/jco.2009.25.8541
|View full text |Cite
|
Sign up to set email alerts
|

Phase II, Randomized Study of Concomitant Chemoradiotherapy Followed by Surgery and Adjuvant Capecitabine Plus Oxaliplatin (CAPOX) Compared With Induction CAPOX Followed by Concomitant Chemoradiotherapy and Surgery in Magnetic Resonance Imaging–Defined, Locally Advanced Rectal Cancer: Grupo Cáncer de Recto 3 Study

Abstract: PURPOSE The optimal therapeutic sequence of the adjuvant chemotherapy component of preoperative chemoradiotherapy (CRT) for patients with locally advanced rectal cancer is controversial. Induction chemotherapy before preoperative CRT may be associated with better efficacy and compliance. PATIENTS AND METHODS A total of 108 patients with locally advanced rectal cancer were randomly assigned to arm A-preoperative CRT with capecitabine, oxaliplatin, and concurrent radiation followed by surgery and four cycles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
240
1
14

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 397 publications
(274 citation statements)
references
References 14 publications
19
240
1
14
Order By: Relevance
“…GCR3 was a randomised phase II study of pre-operative OxCap followed by CRT then surgery vs. CRT then surgery then post-operative OxCap in 108 patients. Less toxicity (p=0.0004) and better compliance (p<0.0001) for the same regimen used as NAC compared with AC was demonstrated [49].…”
Section: Rationale For Neoadjuvant Chemotherapy In Rectal Cancermentioning
confidence: 89%
“…GCR3 was a randomised phase II study of pre-operative OxCap followed by CRT then surgery vs. CRT then surgery then post-operative OxCap in 108 patients. Less toxicity (p=0.0004) and better compliance (p<0.0001) for the same regimen used as NAC compared with AC was demonstrated [49].…”
Section: Rationale For Neoadjuvant Chemotherapy In Rectal Cancermentioning
confidence: 89%
“…Trials of neoadjuvant infusional fluorouracil, leucovorin, and oxaliplatin (FOLFOX) or capecitabine plus oxaliplatin before chemoradiotherapy reported by British and Spanish investigators have demonstrated increased chemotherapy treatment exposure, high response rates, and favorable outcomes. 7,8 On the basis of the results of these trials, as well as our own experiences treating stage IV rectal cancers with FOLFOX, 9 we hypothesized that radiotherapy could be selectively omitted for patients who respond to neoadjuvant FOLFOX and bevacizumab (FOLFOX/ bevacizumab). We were motivated to investigate this strategy both by the possibility of avoiding the toxicities of radiation without compromising local control, and the possibility that earlier introduction of full dose chemotherapy might improve distant control.…”
Section: Journal Of Clinical Oncology O R I G I N a L R E P O R T V Omentioning
confidence: 99%
“…Proven indications exist for the use of intensified chemotherapy as a standard regimen for advanced stage local tumors and expanding tumor growth [12,14,39,40]. The use of an induction chemotherapy followed by standard RCT with 5-FU monotherapy might be more effective concerning tumor response without increasing acute toxicity during RCT [41,42].…”
Section: Discussionmentioning
confidence: 99%